A Simple and Low‐Cost Procedure for Growing Geobacter sulfurreducens Cell Cultures and Biofilms in Bioelectrochemical Systems. Issue 1 (18th November 2016) - O'Brien, J. Patrick; Malvankar, Nikhil S.
Abstract: Anaerobic microorganisms play a central role in several environmental processes and regulate global biogeochemical cycling of nutrients and minerals. Many anaerobic microorganisms are important for the production of bioenergy and biofuels. However, the major hurdle in studying anaerobic microorganisms in the laboratory is the requirement for sophisticated and expensive gassing stations and glove boxes to create and maintain the anaerobic environment. This appendix presents a simple design for a gassing station that can be used readily by an inexperienced investigator for cultivation of anaerobic microorganisms. In addition, this appendix also details the low‐cost assembly of bioelectrochemical systems and outlines a simplified procedure for cultivating and analyzing bacterial cell cultures and biofilms that produce electric current, using Geobacter sulfurreducens as a model organism. © 2016 by John Wiley & Sons, Inc.